High risk of malignant mesothelioma and pleural plaques in subjects born close to ophiolites - Bayram, Mehmet; Dongel, Isa; Bakan, Nur Dilek; Yalççn, Hüseyin; Cevit, Ruhiye; Dumortier, Pascal; Nemery, Benoit (Chest, 2013)
Ophiolites, a special sequence of geologic rock units, are known sources of naturally occurring asbestos. The aim of this study was to test whether the occurrence of malignant mesothelioma (MM) or pleural plaques (PPs) in the province of Sivas, Turkey, is determined by the proximity of the patient's birthplace to ophiolites and, if so, to establish the magnitude of the risk. The birthplaces of patients with MM or PPs (cases) and patients with prostate or breast cancer (control subjects), diagnosed between 2000 and 2010 and identified through a mandatory cancer registry or from hospital records (PPs), were located on a geologic map, and the nearest distance to ophiolites was measured. The relation of MM or PPs with distance to ophiolites was analyzed by logistic regression. Samples of soil and house plaster were determined by x-ray diffraction. Patients with MM (n = 100) or PPs (n = 133) were born significantly nearer to ophiolites (median distance, 4.5 km for men, 0 km for women) than were patients with prostate cancer (n = 161) or breast cancer (n = 139) (median distance, 20 km for both). ORs were 1.6 (men) ( P < .001) and 2.0 (women) ( P < .001) for every 5-km decrease in the distance of birthplace to ophiolites for MM, compared with prostate and breast cancer, respectively. In this area without substantial industrial asbestos use, there is an association between the occurrence of mesothelioma (and of PPs) and the proximity of the subject's birthplace to ophiolites.